Media critiques on the Merauke Integrated Food and Energy state (MIFEE) program: A critical discourse perspective - Wahyudin, Ahmad; Dwi Harjanto, Tofan (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2023)
The study is a critical discourse analysis (CDA) on the media critiques on the implementation of the Merauke Integrated Food and Energy Estate (MIFEE) program. The study is aimed at describing the socio-cultural practices of the news items in the mass media about the MIFEE program. The sociocultural practice analysis is a CDA in the macro level, which is related to contexts outside the texts. Contexts, in this case, include situational contexts, i.e. related to a specific society, culture, or polity. The study is qualitative research; data sources are news items about critiques to the MIFEE; data collection is done by the listening and note taking technique; and data analyses are done by the pragmatic equivalence method. The study is backed by content and semantic data validities. Reliability of the study is assessed by intra- and inter-rater reliability techniques. Findings show that criticques to the MIFEE program can be described under five categories, namely: 1) critiques on the disruption of the forest ecosystem, 2) critiques on the system of the local food, 3) critiques on the violation of human rights, 4) critiques on land forfeiture, and 5) critiques on the failure of the MIFFE program. Keywords: MIFEE, critical discourse analysis (CDA), food resilience and self-provision, indigeneous culture